The Democratic Leadership Model of School Principals in Improving Educational Quality - Maliya Rahma Nur Fatikha; Nurul Latifatul Inayati (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
This study aims to examine the implementation of a democratic leadership model of school principals in improving educational quality at SMK Negeri 3 Klaten and to identify its challenges. The study employed a qualitative approach with a single case study design. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing with triangulation techniques. The results show that the principal applies democratic leadership through participatory decision-making, stakeholder involvement, strengthening teacher professionalism through SIM-PKB and training, and creating a conducive and accountable school climate. This implementation contributes to improved learning quality and public trust. However, challenges include hierarchical school culture, differing stakeholder interests, administrative burdens, and limited external support.